Estudio de la aplicación de un Bioestimulante radicular en el rendimiento de “asparagus officinalis” var. uc-157 f1 en Virú, La Libertad. - Fhon Chávez, Ricardo Gonzalo (2017)
The present work was carried out in Virú, La Libertad, SAVSA, whose objective was to determine the study of the application of a biostimulant that contains auxins, cytokinins and gibberellins, which directly influence the performance and quality of " Asparagus officinalis "Var. UC-157 F1, for which 3 treatments and 1 control were used, obtaining as results in the yield, 611.71 kg. ha-1, and in the qualities had improvements in 4% with respect to the treatment 1 that corresponds to 100 kg. ha-1 and the control-treated control; reaching a yield of 3828.5 kg. ha-1. All this could be validated with the analysis of variance performed obtaining a probability of 0.692102680787189 being this value greater than 0.5.